Expenditure decisions of international tourists to Taiwan: application of the Heckman two-stage approach - Kieu-Thi Phan; Sheng-Hung Chen; Jie-Min Lee; Ca-Van Pham (Cogent Social Sciences, 2024)
Based on a large sample of 30,945 international tourists to Taiwan from 2016 to 2021, this study examines how these tourists make expenditure decisions in Tawan. Simultaneously, we consider various determinants such as travel characteristics, individual characteristics, and satisfaction levels, and the COVID-19 pandemic influence tourists’ decisions regarding their expenditures on accommodation, food, transportation, shopping, and other expenses. Employing a two-stage Heckman approach, the study finds that satisfaction positively affects spending in various categories, highlighting the importance of enhancing visitor satisfaction. Tourists traveling shorter distances allocate more to accommodation, food, and shopping, while repeat visitors prioritize transportation, accommodation, and shopping. Longer stays result in higher transportation and other expenses, while shorter stays lead to increased spending on accommodation, food, and shopping. Gender, age, education, and income levels also influence spending patterns. Moreover, the COVID-19 pandemic disrupted spending, reducing accommodation and transportation expenses but increasing food and shopping spending as tourists adapted to new standards.